Design of Automatic Door Opening Prototype using Recognition Voice - Winarno Fadjar Bastari; Atmiasri; Anugerah Prasetyo Wibowo (BEST, 2022)
Security at the door is very important for everyone. because the door acts as access to enter or exit a private room. Therefore, the key as a door security plays an important role in implementing the security system. With the frequent occurrence of key loss and also the rise of increasingly sophisticated crime rates in breaking into or destroying conventional keys, it becomes a thought for the author to develop a security system that is more private in nature. That is by using an application that is expected to be a security in the form of a password which will certainly be more profitable. The design of this tool is made with Arduino as a processing center and a servo motor to function to move the doorlock. The next stage Arduino will give a command to the servo to open the door. Only certain people who have access passwords can open doors in rooms that use voice recognition. Meanwhile, those who do not have an access password will not be able to unlock the door in the server room. So that the design of a smart door lock tool that uses Arduino-based voice recognition will provide a more computerized level of security and access